2019
DOI: 10.1080/00313831.2019.1595714
|View full text |Cite
|
Sign up to set email alerts
|

Individual Adjustment Needs for Students in Regular Upper Secondary School

Abstract: The aim of this study was to investigate student-environment fit and perceived need of adjustments for students in the regular upper secondary school, with and without a diagnosis. The students (n = 419) were interviewed with the assessment School Setting Interview. The results showed that for seven of the 16 items, 60% or more of the students experienced that the demands of the school environment were not consistent with their abilities. Girls had a greater need of adjustments in eight of nine SSI school acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…To ensure quality in the service provision of educational support, school personnel and/or student health units must have opportunities to identify support needs, and the information on which decisions are made must be adequate (Lebeer et al, 2010). It is suggested that assessments consider the student's interaction with the environment in a systematic way using a needs-based approach (Egilson & Hemmingsson, 2009;Lebeer et al, 2010;Lidström, Hemmingsson & Ekbladh, 2020;Simmeborn Fleischer, Adolfsson & Granlund, 2013). Since a student's participation and need for support is influenced by their perception of the environment in which the activity occurs (Maxwell, Alves & Granlund, 2012), scholars have emphasised the importance of including the experiences of the individual student (Cahill & Beisbier, 2020;Gibson & Kendall, 2010;Hammarberg, 2015;Kramer, Olsen, Mermelstein, Balcells & Liljenquist, 2012;Şahin et al, 2020).…”
Section: Measuring Student-environment Fitmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure quality in the service provision of educational support, school personnel and/or student health units must have opportunities to identify support needs, and the information on which decisions are made must be adequate (Lebeer et al, 2010). It is suggested that assessments consider the student's interaction with the environment in a systematic way using a needs-based approach (Egilson & Hemmingsson, 2009;Lebeer et al, 2010;Lidström, Hemmingsson & Ekbladh, 2020;Simmeborn Fleischer, Adolfsson & Granlund, 2013). Since a student's participation and need for support is influenced by their perception of the environment in which the activity occurs (Maxwell, Alves & Granlund, 2012), scholars have emphasised the importance of including the experiences of the individual student (Cahill & Beisbier, 2020;Gibson & Kendall, 2010;Hammarberg, 2015;Kramer, Olsen, Mermelstein, Balcells & Liljenquist, 2012;Şahin et al, 2020).…”
Section: Measuring Student-environment Fitmentioning
confidence: 99%
“…Taken together, research indicate that students with SEN seem not only to struggle during their educational years but that their difficulties continue into adult life, with an increased risk of poor health outcomes and dependence on the welfare system, compromising their participation in society. The importance of supporting students with SEN in upper secondary school to reduce the risk of future exclusion from the labour market and further studies is therefore stressed, along with the need for studies investigating the longitudinal impact of the support provided to students (DuPaul et al, 2009;Lidström et al, 2020;Tideman et al, 2020).…”
Section: Establishment In Work and Further Studies Among Students Witmentioning
confidence: 99%
“…I en tidigare studie pekar resultatet på brister i identifiering av vilka stödåtgärder som är gynnsamma (Jönsson, 2018). Det bekräftas i intervjuer med gymnasieelever där endast 20 procent upplevde att de fick det stöd de behövde (Yngve et al, 2019): 60 procent uppger bristande anpassningar i lärmiljön (Lidström et al, 2019). En annan intervjustudie med gymnasieelever pekar på svårigheter att få stöd i undervisningen .…”
unclassified